Contrasting Life Traits of Sympatric Calanus glacialis and C. finmarchicus in a Warming Arctic Revealed by a Year-Round Study in Isfjorden, Svalbard - Hatlebakk, Maja K Viddal; Kosobokova, Ksenia N.; Daase, Malin; Søreide, Janne (Frontiers in Marine Science, 2022)
publishedVersion